Loss of p21 does not protect against premature ovarian insufficiency caused by alkylating agents - Lu, Xiaohui; Han, Yongli; Song, Jiaming; Wan, Qin; Liu, Pengfei; Chen, Li; Wang, Yufeng; Xue, Pingping; Dai, Xiuliang (Frontiers in Endocrinology, 2025)
BackgroundRecent studies have focused on investigating the role of cellular senescence in ovarian aging. Targeting cellular senescence has been proposed as a potential strategy to improve ovarian aging. p16 and p21 are classical molecules involved in mediating cellular senescence. In our previous study, we demonstrated that ablation of p16 is dispensable for premature ovarian aging induced by alkylating agents. In the present study, we investigated whether p21 deficiency could mitigate ovarian aging caused by alkylating agents.MethodsEight-week-old wild-type (WT, n=7) and p21 knockout (KO, n=7) female mice received a single injection of busulfan (BUL, 30 mg/kg) and cyclophosphamide (CTX, 120 mg/kg) to induce premature ovarian insufficiency (POI). Untreated WT (n=4) and p21 KO (n=4) mice served as controls. Ovaries were analyzed thirteen weeks after treatment. Ovarian reserve, folliculogenesis, cell proliferation, apoptosis and senescence, multinucleated giant cells (MGCs) and their characteristics, pro-inflammatory factors, fibrosis, ovarian stromal cell properties, and the expression of cell cycle inhibitors, including p16, p19, p27, and p53, were evaluated.ResultsFemale mice treated with alkylating agents exhibited typical features of POI, including a dramatic reduction in the number of primordial and growing follicles; defective folliculogenesis characterized by growth arrest in early-stage follicles, extensive atresia in mid-stage follicles, dysregulated FSH receptor (FSHr) expression in antral follicles, and abnormal over-activation of primordial follicles; the presence of hemosiderin-laden MGCs and fibrosis in the ovarian cortical region. p21 deficiency did not significantly mitigate these phenotypes. There were no significantly differences in the expression of pro-inflammatory factors, folliculogenesis-regulating factors, or steroidogenesis-related factors and cell cycle inhibitors between WT and p21 KO mice treated with alkylating agents. In addition, p21 deficiency did not prevent alkylating agent-induced cellular senescence.ConclusionThese results demonstrated that p21 is dispensable for POI caused by alkylating agents, suggesting that targeting p21 alone may not mitigate ovarian aging caused by alkylating agents.